Phenolic content and free radical scavenging activities in rambutan during fruit maturation - Thitilertdecha N. (2014)
The 1,1-diphenyl-2-picrylhydrazyl (DPPH•) scavenging activity, changes and accumulation of phenolic content were studied in the peel, seed and pulp of rambutan, Nephelium lappaceum L. (Rongrien and Seeechompoo cultivars) during fruit maturation. The IC50 values of the radical scavenging activity of the peels, in both cultivars remained low through fruit development (1.42-4.75 μg/mL) but the values of the seed and pulps were low at the beginning and increased markedly toward fruit development until harvest (4.87 to >1000 μg/mL). The accumulation of phenolic compounds in rambutan peels of Rongrien and Seechompoo cultivars increased continuously until reaching a maximum of 1653 and 733 mg per fruit at the time of being harvested, at 112 and 98 days after full bloom (DAFB), respectively. Ellagic acid, corilagin and geraniin in the peels of both cultivars were observed and quantified. The major component in the peels of the two cultivars was geraniin. The accumulation of ellagic acid, corilagin and geraniin in the peels increased and reached the maximum at the harvest stage, especially the major constituent of geraniin (1011 and 444 mg/fruit for Rongrien and Seechompoo, respectively). The free radical scavenging property was observed to have a relationship with the phenolic content quantified in different parts of the rambutan fruit. This research demonstrates potential data on phenolic constituents through fruit development, especially in the peels at the time of harvest. © 2011 Elsevier B.V. All rights reserved.